Substance Painter to Unreal Engine 5 masterclass. (Packt Publishing, 2022)
Learn how to create game assets in Substance Painter and Unreal Engine 5 in this all-in-one masterclass. About This Video Using UE5 Niagara particle system to create fire simulations and fireflies Material creation for foliage, terrain, and more Rendering assets in Substance and creating an environmental presentation video in UE5 In Detail Unreal Engine is a complete suite of creation tools for game development, architectural and automotive visualization, linear film and television content creation, broadcast and live event production, training and simulation, and other real-time applications. This course is one of the most up-to-date out there and will be using the latest tech to bring you cutting-edge content in the 3D industry, which includes 3D texturing. Learn all about UDIM map workflow and why it is such a game-changer. It will also focus on the foundation of 3D modeling, which includes UVs and the mapping process. A massive part of the course is devoted to setting up your models correctly. High and low poly workflows, not forgetting optimizing your assets to create triple AAA-level models. We will look at how to import and use textures created specifically for Unreal Engine and use them to create the materials for our stylized wagon game asset. 'Master the Art of Substance Painter and Unreal Engine 5 will also be an introduction to setting files to create a clean UI. The skills you learn here are fully transferable to all your future builds. In the end, you will come away with the knowledge and skills to create this stylized wagon scene from scratch. So, come give us a try and be blown away by just how much you can achieve from one course. Audience This course is for beginner 3D modeling artists and game designers eager to learn how to texture a stylized wagon and place it in a stylized campfire scene; enthusiasts of Unreal Engine 5 (UE5) who want to fast-track their understanding of its new and exciting changes; and beginner to mid-level 3D modelers who want to take their modeling to a new level and improve their workflow with tips and tricks.